2018
DOI: 10.1159/000487239
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Imaging Does Not Reliably Predict Macroscopic Extranodal Extension in Human Papilloma Virus-Associated Oropharyngeal Cancer

Abstract: Background: Radiographic concern for lymphatic extranodal extension (ENE) impacts upfront management decisions for patients with human papilloma virus (HPV) oropharyngeal squamous cell carcinoma (OPSCC). Therefore, we set out to evaluate the accuracy of preoperative contrast-enhanced computed tomography (CECT) to predict major ENE (> 2 mm). Methods: Twenty-seven consecutive patients with HPV-associated OPSCC who presented at our institutional multidisciplinary tumor board were staged radiographically with posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 15 publications
(25 reference statements)
0
46
0
Order By: Relevance
“…Multiple studies have investigated the accuracy of CT in identifying ECS, (Table ) however, only a limited number of studies have focused on ECS in P16 + OPSCC which has implications for accuracy due to the differing clinical and radiological features, and for how this knowledge is applied to clinical practice as other cancers, such as cutaneous SCC, are readily amenable to resection. Geltzeiler et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have investigated the accuracy of CT in identifying ECS, (Table ) however, only a limited number of studies have focused on ECS in P16 + OPSCC which has implications for accuracy due to the differing clinical and radiological features, and for how this knowledge is applied to clinical practice as other cancers, such as cutaneous SCC, are readily amenable to resection. Geltzeiler et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a smaller cohort study of 27 patients, Patel et al . evaluated the accuracy of CT to predict macroscopic ECS (>2 mm) . For two radiologists, the sensitivities were 88% and 100% (PPV = 43.8 and 53.3%); however, specificities were 52.6% and 63.2% (NPV = 90.9 and 53.3%).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were performed using HNSCC from heterogenous or undefined anatomic subsites and did not account for the role of HPV status. To our knowledge, three studies have investigated the performance of cCT in predicting ENE . Geltzeiler et al found the presence of three or more radiologically suspicious lymph nodes to be strongly associated with ENE (positive predictive value [PPV] = 91%), whereas Patel et al found the interruption of the capsule and invasion into the perinodal fat to be poorly predictive of ENE (PPV = 44–55%).…”
Section: Introductionmentioning
confidence: 99%
“…Full text review of these articles identified seven studies to be used for qualitative and quantitative analysis. [22][23][24][25][26][27][28] A summary of the search process is shown in Figure 1. All seven studies were of level 2 evidence based on the Oxford Level of Evidence criteria.…”
Section: Search Resultsmentioning
confidence: 99%
“…In some cases, evaluating HPV-positive diseases with the same criteria used for HPV-negative disease may have led to inconsistencies among radiologists. 27 There is no standardized method to score rENE. However, commonly used assessment criteria include internal lymph node characteristics, perinodal stranding, irregular nodal margins, matted nodes, gross adjacent invasion, and nodal size.…”
Section: Discussionmentioning
confidence: 99%